Roles of the Mesenchymal Stromal/Stem Cell Marker Meflin/Islr in Cancer Fibrosis - Takahashi, Masahide; Kobayashi, Hiroki; Mizutani, Yasuyuki; Hara, Akitoshi; Iida, Tadashi; Miyai, Yuki; Asai, Naoya; Enomoto, Atsushi (Frontiers in Cell and Developmental Biology, 2021)
Fibroblasts synthesise the extracellular matrix (ECM) such as collagen and elastin, the excessive accumulation of which can lead to fibrosis and organ dysfunction under pathological conditions. Cancer-associated fibroblasts (CAFs) are major constituents of the tumour microenvironment (TME) that accompany the desmoplastic reaction responsible for anti-cancer treatment resistance. Thus, it is important to dissect the roles of CAFs in the TME to develop new therapeutic strategies for refractory cancers. Recent progress in the studies of CAF biology suggests that the functions of CAFs are complicated and that they are composed of functionally distinct populations, including cancer-promoting CAFs (pCAFs) and cancer-restraining CAFs (rCAFs). We recently identified a new cell surface marker for rCAFs in pancreatic and colon cancers, designated as Meflin (mesenchymal stromal cell- and fibroblast-expressing Linx paralogue)/Islr (immunoglobulin super family containing leucine-rich repeat). Based on the distribution of Meflin/Islr-positive cells, we also considered it a specific candidate marker for mesenchymal stroma/stem cells. Meflin/Islr-positive CAFs have been shown to suppress cancer progression by being involved in regulating collagen structures and BMP signalling in the TME. This review describes the function of Meflin/Islr in cancer fibrosis as well as in cardiac and lung fibrosis and its potential in the development of new cancer therapeutics.